Analisis Faktor Human Error dalam Kecelakaan Lalu Lintas dan Pertanggungjawaban Hukumnya - Mohammad Reza Setiawan; Muhammad Rizal Rustam (Decisio: Jurnal Ilmiah Hukum, 2025)
Traffic accidents remain a serious issue globally, including in Indonesia, with human error being the dominant factor. Fatigue, lack of concentration, traffic violations, and external influences such as alcohol contribute significantly to accident rates. Legal responsibility for human error-related accidents is regulated in Indonesian law through criminal, civil, and administrative sanctions. However, the effectiveness of law enforcement remains a challenge due to low legal awareness and inconsistent regulatory implementation. This study employs a normative juridical approach by analyzing regulations, court decisions, and previous research to assess the legal framework governing traffic accidents caused by human error. Data were collected through literature studies and analyzed qualitatively to classify legal sources into primary, secondary, and tertiary categories. The findings indicate that despite the existing legal framework, gaps in enforcement reduce its deterrent effect. Strengthening legal awareness, implementing stricter law enforcement, and integrating technological solutions are necessary to enhance traffic safety. This study contributes to the development of more effective policies in addressing human error-related traffic accidents and improving public compliance with traffic regulations.